Hybrid graphene-BC2N monolayers and nanoribbons with extended line defects: An ab initio study. (February 2017) - Guerra, T.; Azevedo, S.; Machado, M.
Abstract: Opening a bandgap in graphene is probably one of the most important and urgent topics in the graphene research currently, since most of the proposed applications for graphene in nanoelectronic devices require the ability to adjust its bandgap. In this work we perform first-principles calculations to investigate the alterations at the structural, energetic, electronic and magnetic properties of hybrid graphene-BC2 N monolayers (GBMLs) and zigzag graphene-BC2 N nanoribbons (ZGBNRs) with different types of extended line defects (ELDs) at the grain boundary. Different reconstruction processes are observed forming different types of ELDs depending on the nature of the atoms into the grain boundary as well as the structures type, arrangement, position/size of domains, and inserted atoms. The inclusion of these ELDs creates edge type effects in the ELD at GBNMLs, inducing spin polarization and localization of states at the Fermi level. GBNMLs show a wide range of electronic structures going from semimetallic to semiconducting and metallic, which can have magnetic ground states with ferromagnetic and antiferromagnetic. ZGBNRs are always metallic with ferromagnetic coupling between carbon atoms at the structures edges. Abstract : Highlights: The hybrid graphene-BC2 N (GBC2 N) systems offer new possibilities of tuning the bandgap. The inclusion of extended line defects in GBC2 N can create type-edge effects. The magnetic moment depends on the imbalance of C atoms between different sublattices.